PENGARUH MOTIVASI KERJA, SOFT SKILL, EFIKASI DIRI DAN LITERASI DIGITAL TERHADAP KESIAPAN KERJA - Tifani Adelia; Ahmad Mardalis (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
The purpose of this study was to analyze the effect of work motivation, soft skills, self-efficacy and digital literacy on student work readiness (case study of UMS management students class of 2020). The method used in this research is a quantitative method with 234 respondents. The population in this study were students of the management study program at the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta class of 2020. The sampling technique used is purposive sampling, the data used is promer data obtained through respondents' answers using a closed type of interview or questionnaire, the sampling technique in this study uses the Slovin formula. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software.  PLS-SEM analysis consists of two Outer model and Inner model. The results of this study indicate that work motivation has no effect on the work readiness of management students of Universitas Muhammadiyah Surakarta Class of 2020. soft skills, self-efficacy, and digital literacy have a positive and significant effect on the work readiness of Universitas Muhammadiyah Surakarta Class of 2020 management students.